The Effect of Leadership Style and Compensation on Employee Performance at Seameo Seamolec in Tangerang Selatan - Suyatin Suyatin; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Peneliti.net, 2022)
This study aims to determine the effect of leadership style and compensation on the work performance of SEAMEO SEAMOLEC employees partially and simultaneously. This research is a descriptive quantitative analysis with an approach to employees. The population in this study were 64 SEAMEO SEAMOLEC employees. The sample used in this research is using nonprobability sampling technique or saturated sampling method. The data collection procedure in this study was using a questionnaire using a Likert scale and SPSS 24 programming. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression tests, t tests, F tests and coefficients of determination test. The research results that can be presented are: (1) there is an influence of leadership style on performance (tcount 8.116 > ttable 1.999), (2) there is an effect of compensation on performance (tcount 7.174 > ttable 1.999), and (3) the influence of leadership style and compensation on performance. Employee work performance (Fcount 40.339 > Ftable 3.148). So that it shows that leadership style and compensation at SEAMEO SEAMOLEC partially and simultaneously have a positive and significant effect on work performance